The future is the beginning the words and wisdom of Bob Marley - Marley, Bob 1945-1981 (Harmony Books, 2012)
In this one-of-a-kind collection, the words of reggae legend Bob Marley are brought together as a testament to the deeply felt and powerfully motivated sense of spirit of the revered singer-songwriter and performer who helped spread both Jamaican music and the Rastafarian movement across the world. The texts, many never before published in book form, were gathered at 56 Hope Road, Kingston, Jamaica, where Bob lived and worked in the 1970s. In addition to a Grammy Lifetime Achievement Award, Marley was awarded a United Nations Medal of Peace. Bob Marley's wisdom came not only through his songs but also from his poetic, spoken words. The short selections in this book, which are compiled from interviews he gave over the years, will give readers a true sense of who Bob Marley really was and are bound to inspire them with his timeless message of faith, unity, and love.--From publisher description
Keywords: Marley, Bob; Marley, Bob / Quotations; Marley, Bob / Philosophy; Reggae musicians / Quotations; Philosophie